2017
DOI: 10.1002/2017gb005733
|View full text |Cite
|
Sign up to set email alerts
|

Response of Water Use Efficiency to Global Environmental Change Based on Output From Terrestrial Biosphere Models

Abstract: Water use efficiency (WUE), defined as the ratio of gross primary productivity and evapotranspiration at the ecosystem scale, is a critical variable linking the carbon and water cycles. Incorporating a dependency on vapor pressure deficit, apparent underlying WUE (uWUE) provides a better indicator of how terrestrial ecosystems respond to environmental changes than other WUE formulations. Here we used 20th century simulations from four terrestrial biosphere models to develop a novel variance decomposition metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 66 publications
(107 reference statements)
1
34
1
Order By: Relevance
“…The discrepancy in those studies could be partly attributed to the different environmental conditions, plant species, planting areas and cultivation methods. Moreover, the significant increasing trend (8.5 × 10 −3 g C kg −1 H 2 O per year) of annual WUE found in this study which may be due to the increased atmospheric CO 2 concentration [17,55,56]. However, the WUE trend was much higher than Sun et al (2018) (7.32 × 10 −4 g C kg −1 H 2 O per year) [30] which may induced by their different data sources.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The discrepancy in those studies could be partly attributed to the different environmental conditions, plant species, planting areas and cultivation methods. Moreover, the significant increasing trend (8.5 × 10 −3 g C kg −1 H 2 O per year) of annual WUE found in this study which may be due to the increased atmospheric CO 2 concentration [17,55,56]. However, the WUE trend was much higher than Sun et al (2018) (7.32 × 10 −4 g C kg −1 H 2 O per year) [30] which may induced by their different data sources.…”
Section: Discussioncontrasting
confidence: 64%
“…Many previous studies have investigated the spatiotemporal changes of WUE. For example, Zhou et al (2017) showed that underlying WUE (GPP × VPD 0.5 /ET) increased slowly during 1901-1975 but increased rapidly from 1976 to 2010 over the world based on terrestrial biosphere models [17]. Tang et al (2014) found that the WUE had a similar latitudinal trend on earth, increasing from the subtropics to about 51 • N and then decreased in higher latitudes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Increased WUE in forests under eCO 2 has been reported in many previous studies, including those using field experiments (De Kauwe et al, ; Leakey et al, ), tree ring measurements (Dekker et al, ; D. C. Frank et al, ; Saurer et al, ), isotopic compositions of atmospheric CO 2 (Keeling et al, ), eddy covariance (EC) flux tower measurements (Keenan et al, ; Mastrotheodoros et al, ) and model simulations (Cheng et al, ; Huang et al, ; Zhou et al, ). However, these studies have not consistently agreed with the statement that increased WUE under eCO 2 should correspond to increased carbon assimilation and/or decreased water losses in forests.…”
Section: Introductionmentioning
confidence: 75%
“…; Zhou et al . ). Land‐cover change can alter ecosystem water‐use efficiency, for example, by changing the balance between C 3 and C 4 vegetation, by replacing annual with perennial species, or by changing canopy structure and leaf area index in such a way that it impacts the partitioning between evaporation and transpiration at the ecosystem level (Nosetto et al .…”
Section: Gas Exchange and Water‐use Efficiency In Response To Global mentioning
confidence: 99%
“…Recent estimates suggest that the overall contribution of land‐cover change since 1900 has been to reduce water‐use efficiency of terrestrial ecosystems, on average, compared to what it would be in the absence of land‐cover change (Zhou et al . ).…”
Section: Gas Exchange and Water‐use Efficiency In Response To Global mentioning
confidence: 99%